Morphological characterization of fruits, seeds and post-seminal development of avocado - Oliveira, Inez Vilar de Morais; Costa, Raquel Silva; Môro, Fabíola Vitti; Martins, Antonio Baldo Geraldo; Silva, Raissa Rachel Salustriano da (Federal University of Piauí, 2010)
Avocado propagation is commercialy realized by grafting of the desirable variety in seminal rootstocks. However, the literature is discordant about the occurrence of poliembriony and type of fruit of this specie. In function of this, as research had the objective to characterize the type of fruit, seed morphological aspects and the seedling nurse, besides to evaluate the number of embryos existent. The avocado fruit is a berry. The seeds are monoembryonics and exalbuminous. The germination is hipogeal and the emergene of the seedling occurred 33 days after sowing. The primary root is long and white and the secondary roots are short and filiforns.  The cotyledons are massive and pinkish. It was possible to observe the presence of multi-stem in avocado seed, originated from the collar. The seeds present multi-stems; the beginning of seedling emergence stabilization occurred in the eighth week, being unviable for propagation of this species to keep these seeds in the nursery for more time.